IDA Regional Window Program 2003-17 - Independent Evaluation Group (World Bank, Washington, DC, 2019)
The International Development Association (IDA) Regional Window Program was developed as a funding mechanism to provide additional financing resources to co‐finance projects that help low‐income countries achieve their regional integration objectives. The main objective of this synthesis report is to inform policy decisions on the International Development Association (IDA) Regional Window Program in the context of the IDA18 mid‐term review and the IDA19 replenishment. The report contains information on (a) the achievements of the program, and (b) key findings and conclusions for the consideration of IDA Deputies. This synthesis is derived primarily from IEG’s thematic evaluation, Two to Tango: An IEG Independent Evaluation of World Bank Group Support to Fostering Regional Integration and is complemented by findings from other existing thematic evaluations such as Grow with the flow: World Bank Group support to Trade Facilitation, project‐level evaluations and validations, and project performance assessment reports.